Roles of Nigerian women trust fund on women's political representation in Imo state House of Assembly - Ewuru, Chinazo Destiny (2022)
The current research tends to examine the challenges and effectiveness of Nigerian Women Trust Fund strategies on women's political representation in the Imo State House of Assembly as well as explore how these strategies can increase women's political representation in the Imo state House of Assembly. A qualitative case study approach was used, and the informants were selected using purposive sampling, and the inclusion criteria were experience, ability, and comprehension. The eleven informants were interviewed, drawn from top management and administrative members of the Nigerian Women Trust Fund, academics, grassroots women, and present and past members of the Imo State House of Assembly, while thematic analysis was used to analyze the data. The research found that the strategies used by the Nigerian Women Trust Fund included ensuring quota representation of women in the state house assembly, mobilization, provision of financial support, support of grassroots organizations that have the interest of women, as well as advocacy through domestic lobbying and awareness. The research also found that Nigerian Women Trust Fund has impacted women's lives through political mentorship, capacity-building program, financial support, and importantly, creating women's rights awareness even though the socio-economic/political challenges hinder the effective political representation of women in the Imo state House of Assembly. Besides, political violence and lack of education remain significant challenges to NWTF's quest for women's political representation. Finally, the study provided valuable insight into the role of the Nigerian Women Trust Fund and strategies that can be adopted by the NGOs to ensure adequate women's political representation.